Revisiting the Role of KUA: Reducing Child Marriage through the Perspectives of Maqasid al-Shariah and the Sociology of Islamic Law - Kartini, Kartini; Iswandi, Iswandi (Jurnal Adabiyah, 2025)
This study aims to analyze the effectiveness of prevention programs implemented by the KUA (Religious Affairs Office), evaluate the forms of collaboration between agencies and the community, and interpret the role of these institutions through the perspective of Maqasid al-Syariah and the sociology of Islamic law. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with the head of the KUA, religious leaders, and religious instructors, and strengthened by field observations and documentation studies. Analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through a process of data reduction, data presentation, and drawing conclusions linked to the theoretical framework. The results show that the socialization and counseling programs implemented by the KUA are still conventional, focusing on lecture methods, and have not reached vulnerable groups such as adolescents in schools. The implementation of marriage document audits has been underway, but marriage dispensations and the practice of unregistered marriages remain a loophole exploited by the community. Furthermore, cross-sectoral coordination with educational institutions, health institutions, and village governments has not been systematically established, resulting in partial and administrative efforts to prevent child marriage. The implications of this study emphasize the importance of repositioning the role of the Office of Religious Affairs (KUA) as an agent of social change by strengthening its educational and preventive functions, expanding institutional collaboration, and developing a more contextual premarital curriculum. Integrating the values ​​of Maqasid al-Shariah—particularly the protection of life (hifz al-nafs), reason (hifz al-‘aql), and offspring (hifz al-nasl)—with an Islamic legal sociology perspective that emphasizes the dynamics of living law, can serve as a normative and sociological foundation for strengthening the national strategy for preventing child marriage. ملخص تهدف هذه الدراسة إلى تحليل فعالية برامج الوقاية التي ينفذها مكتب الشؤون الدينية (KUA)، وتقييم أشكال التعاون بين الجهات والمجتمع، وتفسير دور هذه المؤسسات من منظور مقاصد الشريعة وعلم اجتماع الشريعة الإسلامية. تعتمد هذه الدراسة على منهج نوعي ودراسة حالة. جُمعت البيانات من خلال مقابلات معمقة مع رئيس مكتب الشؤون الدينية، والقادة الدينيين، والمعلمين الدينيين، ودُعمت بالملاحظات الميدانية ودراسات التوثيق. أُجري التحليل باستخدام نموذج مايلز وهوبرمان وسالدانا التفاعلي، من خلال عملية اختزال البيانات وعرضها، واستخلاص استنتاجات مرتبطة بالإطار النظري. تُظهر النتائج أن برامج التنشئة الاجتماعية والإرشاد التي ينفذها مكتب الشؤون الدينية لا تزال تقليدية، وتركز على أساليب المحاضرات، ولم تصل إلى الفئات الضعيفة مثل المراهقين في المدارس. لا يزال تنفيذ عمليات تدقيق وثائق الزواج مستمرًا، إلا أن إعفاءات الزواج وممارسة الزواج غير المسجل لا تزال تُمثل ثغرة يستغلها المجتمع. علاوة على ذلك، لم يُرسَ التنسيق بين القطاعات مع المؤسسات التعليمية والصحية وحكومات القرى بانتظام، مما أدى إلى بذل جهود جزئية وإدارية لمنع زواج الأطفال. وتؤكد آثار هذه الدراسة على أهمية إعادة تحديد دور مكتب الشؤون الدينية (KUA) كعامل للتغيير الاجتماعي من خلال تعزيز وظائفه التعليمية والوقائية، وتوسيع التعاون المؤسسي، وتطوير منهج دراسي أكثر ملاءمة للسياق قبل الزواج. إن دمج قيم مقاصد الشريعة الإسلامية - وخاصةً حفظ النفس والعقل والنسل - مع منظور علم الاجتماع القانوني الإسلامي الذي يُركز على ديناميكيات القانون الحي، يمكن أن يُشكل أساسًا معياريًا وسوسيولوجيًا لتعزيز الاستراتيجية الوطنية لمنع زواج الأطفال. Abstrak Penelitian ini bertujuan untuk menganalisis efektivitas program pencegahan yang dilaksanakan KUA, mengevaluasi bentuk kolaborasi antar instansi maupun masyarakat, serta menafsirkan peran kelembagaan tersebut melalui perspektif Maqasid al-Syariah dan sosiologi hukum Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara mendalam dengan kepala KUA, penghulu, dan penyuluh agama, serta diperkuat dengan observasi lapangan dan studi dokumentasi. Analisis dilakukan dengan model interaktif Miles, Huberman, dan Saldaña melalui proses reduksi data, penyajian data, dan penarikan kesimpulan yang dihubungkan dengan kerangka teori. Hasil penelitian menunjukkan bahwa program sosialisasi dan penyuluhan yang dijalankan KUA masih bersifat konvensional, berfokus pada metode ceramah, dan belum menyentuh kelompok rentan seperti remaja di sekolah. Implementasi pemeriksaan dokumen perkawinan telah berjalan, namun dispensasi nikah dan praktik nikah siri masih menjadi celah yang dimanfaatkan masyarakat. Selain itu, koordinasi lintas sektor dengan lembaga pendidikan, kesehatan, maupun pemerintah desa belum terbangun secara sistematis sehingga upaya pencegahan perkawinan anak cenderung parsial dan administratif. Implikasi penelitian ini menegaskan pentingnya reposisi peran KUA sebagai agen perubahan sosial dengan memperkuat fungsi edukatif dan preventif, memperluas kolaborasi kelembagaan, serta mengembangkan kurikulum pranikah yang lebih kontekstual. Integrasi nilai-nilai Maqasid al-Syariah—khususnya perlindungan jiwa (hifz al-nafs), akal (hifz al-‘aql), dan keturunan (hifz al-nasl)—bersama perspektif sosiologi hukum Islam yang menekankan dinamika living law, dapat menjadi fondasi normatif dan sosiologis dalam memperkuat strategi nasional pencegahan perkawinan anak.